Analisis Kelayakan Usaha Ternak Kelinci menggunakan Fodder Jagung sebagai Pakan Substitusi: Feasibility Analysis of Rabbit Farming using Corn Fodder as Feed Substitute - Sritiasni Sritiasni; Avonita Jihan; Bangkit Lutfiaji Syaefullah (Politeknik Pertanian Bogor, 2022)
This study aims to increase public knowledge about how to analyze the feasibility of rabbit farming using corn fodder in Aimasi Village, Prafi District, Manokwari Regency. This research was carried out from April to May 2022. The data analysis technique used in this study is qualitative analysis by means of research that produces descriptive data, which is stated by verbal information. The variables measured are BEP (Break Even Point), R/C ratio (Revenue Cost Ratio), HPP (Cost of Production), and IOFC (Income Over Feed Cost). The results showed that the unit BEP value was 0,13 the rupiah BEP value was Rp62.648, the R/C was 1,89, the HPP value was Rp375.577 the IOFC value was Rp1.354.200 the conclusion shows that the resulting value is greater than the cost of production, so the rabbit farming analysis using corn fodder as a substitute feed is very feasible.